Heavy Metals Assessment in the Medjerda River Basin (Northeastern Algeria): A Preliminary Water Analysis and Toad Skin Biopsy - Guezgouz, N; Parisi, C; Boubsil, S; Grieco, G; Soualah, A. H; Guerriero, G (My University, 2020)
Our study attempted to monitor the quality of water in Medjarda basin (Northeastern Algeria) and to provide baseline information of heavy metals in the water as well as in a potential amphibian biosentinel, the spiny toad, Bufo spinosus. We measured pH, temperature, dissolved oxygen and biological oxygen demand of water and levels of heavy metals in toad skin using an atomic absorption flame spectrophotometer. Lead (Pb) concentration in water and in toad skin at all sites exceeded respectively 60 and 96 times the standard reference values. The heavy metal concentrations, in descending order, in water and in male toad skin were as follows: Pb[Fe[ Cu[Zn and Fe[Pb[Zn[Cu respectively. This study highlights the ecological status of the surrounding areas upstream of the Medjarda basin as being a point source of heavy metal pollution. It is further stated that a non-invasive skin removal is an ethically sound technique to evaluate heavy metal accumulation in aquatic animals like